2014
DOI: 10.1186/s12870-014-0258-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of next-generation sequencing technology to study genetic diversity and identify unique SNP markers in bread wheat from Kazakhstan

Abstract: BackgroundNew SNP marker platforms offer the opportunity to investigate the relationships between wheat cultivars from different regions and assess the mechanism and processes that have led to adaptation to particular production environments. Wheat breeding has a long history in Kazakhstan and the aim of this study was to explore the relationship between key varieties from Kazakhstan and germplasm from breeding programs for other regions.ResultsThe study revealed 5,898 polymorphic markers amongst ten cultivars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
5
16
0
Order By: Relevance
“…The highest average number of alleles was detected in the B genome, followed by the D genome and the A genome, using 17 SSR markers, as reported by Salem et al (2015) [36]. In the present study, we obtained 24,767 SNPs markers and observed the lowest frequency of SNPs in the D genomes, whereas the B genome contained the highest frequency of polymorphic markers, which is in agreement with the results of previous studies [1,19,28,32,37,38,[39][40][41]. Furthermore, the fewest SNP markers were located on chromosome 4D, whereas the highest number of SNP markers were located on chromosome 3B, as reported by Saintenac has the lowest number.…”
Section: Discussionsupporting
confidence: 92%
“…The highest average number of alleles was detected in the B genome, followed by the D genome and the A genome, using 17 SSR markers, as reported by Salem et al (2015) [36]. In the present study, we obtained 24,767 SNPs markers and observed the lowest frequency of SNPs in the D genomes, whereas the B genome contained the highest frequency of polymorphic markers, which is in agreement with the results of previous studies [1,19,28,32,37,38,[39][40][41]. Furthermore, the fewest SNP markers were located on chromosome 4D, whereas the highest number of SNP markers were located on chromosome 3B, as reported by Saintenac has the lowest number.…”
Section: Discussionsupporting
confidence: 92%
“…Using the POPSEQ approach, we ordered 11,758 (∼71.24%) and 14,697 (∼89.04%) SNPs to the W7984 and CSSS assemblies, respectively, which were much higher than these reported (22.5–46.3%) in previous studies ( Würschum et al, 2013 ; Shavrukov et al, 2014 ; Wang et al, 2014 ). Edae et al (2015) obtained 33,664 SNPs with up to 80% missing data from W7984 × Opata M85 RIL population out of which, 16,591 (49.3%) and 9709 (28.8%) SNPs were mapped to the W7984 and CSSS reference assemblies, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…Fifty markers have not yet been mapped in the wheat genome. Shavrukov et al (2014) used wheat varieties from Kazakhstan and the SNP platform Infinium 9k (Illumina) for wheat and identified 46% informative markers. In their work, 49% were associated with the A genome, 46% with the B genome, and 5% with the D genome.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat germplasm evaluation with SNP markers is just beginning, and only few works have been published using this marker in wheat, e.g. Shavrukov (2014) in Kazakstan.…”
Section: Introductionmentioning
confidence: 99%